Pengembangan Sistem Informasi Pemesanan Barang pada Distributor Cat Menggunakan Metode Pengembangan Personal Extreme Programming (Studi Kasus: PD. Sentosa Kota Bandung) - Ahmad Wicaksana; Satrio Agung Wicaksono; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Sentosa is a Small and Medium Enterprise that runs its business as one of paint distributor in Bandung. In running its business, the enterprise has implemented some business rules that cause some problems, which includes no mechanism available for Sales to take over order taking, invalidated order is still being passed and payments being mixed up From the stated problems, a system is developed as a solution for the problems using the development method of Personal Extreme Programming. Requirement Analysis being done resulted in 41 functional requirements and 2 non-functional requirements. Planning results in 42 tasks with total estimated work time of 116 hours. There are in total 3 iterations in this development. Design results in the creation of 3 use case diagrams, 37 use case scenarios, 17 analysis classes, 14 sequence diagrams, 12 class diagrams and 3 physical data model. Validation testing is done in all iterations, which generated 75 test case, which results in success in all test case. In the final iteration, two types of UAT has been done, UAT for Web System and UAT for Mobile System. UAT for Web System is conducted with 4 respondents with final result of 3.858 (Neutral). UAT for Mobile System is conducted with 3 respondents with final result of 3.444 (Partially Disagree). In the whole iteration, it is noted that real work time clocked in 170 hours and 59 minutes, in which difference in estimated time is due to revision that occurred while designing and obstructions occurred when implementing.